2014
DOI: 10.1002/mma.3216
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of delayed coupled reaction-diffusion systems on networks

Abstract: In this paper, the exponential synchronization problem of delayed coupled reaction‐diffusion systems on networks (DCRDSNs) is investigated. Based on graph theory, a systematic method is designed to achieve exponential synchronization between two DCRDSNs by constructing a global Lyapunov function for error system. Two different kinds of sufficient synchronization criteria are derived in the form of Lyapunov functions and coefficients of drive‐response systems, respectively. Finally, a numerical example is given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…where c k is the cofactor of the k-th diagonal element of the Laplacian matrix of digraph  with weight matrix D. Noting that digraph  with weight matrix D is strongly connected, we have c k > 0 for any k ∈ by Lemma 1. Next, according to conditions (5), (6), and V (2) k (t) ⩾ 0, we get that…”
Section: Lyapunov-type Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…where c k is the cofactor of the k-th diagonal element of the Laplacian matrix of digraph  with weight matrix D. Noting that digraph  with weight matrix D is strongly connected, we have c k > 0 for any k ∈ by Lemma 1. Next, according to conditions (5), (6), and V (2) k (t) ⩾ 0, we get that…”
Section: Lyapunov-type Theoremmentioning
confidence: 99%
“…[1][2][3][4] It has been observed that time delay is an intrinsic part of the coupled system since it unavoidably exists in information transmission between subsystems. 5,6 Therefore, it is desirable to incorporate time delay into CSNs to simulate more realistic networks. Recent studies on coupled systems with time delay have shown that delay may cause undesirable dynamic behaviors such as oscillation and instability.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronization has become an active research subject in nonlinear science. The current problems of synchronization are very interesting, non-traditional, and indeed very challenging [4][5][6][7]. Many scientists who are interested in this field have struggled to achieve the synchronization of different fractional-order chaotic systems [8], mainly due to its potential applications in secure communication and cryptography [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Synchronization can be described as a process, in which all the nodes seek to adjust a certain property of their motion to a common behavior in the limit as time tends to infinity. Over the past 10 years, many network models (for example, static network model [11,12], time-varying network model [13,14], delayed network model [15][16][17], etc.) and synchronization patterns (for example, projective synchronization [18,19], exponential synchronization [20], cluster synchronization [21,22], lag synchronization [23], etc.)…”
mentioning
confidence: 99%